2020
DOI: 10.1051/m2an/2019091
|View full text |Cite
|
Sign up to set email alerts
|

Localization and geometrization in plasmon resonances and geometric structures of Neumann-Poincaré eigenfunctions

Abstract: This paper reports some novel and intriguing discoveries about the localization and geometrization phenomenon in plasmon resonances and the intrinsic geometric structures of Neumann-Poincaré eigenfunctions. It is known that plasmon resonance generically occurs in the quasi-static regime where the size of the plasmonic inclusion is sufficiently small compared to the wavelength. In this paper, we show that the global smallness condition on the plasmonic inclusion can be replaced by a local high-curvature conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…We refer to [10,11,36,47,50,53] and the references cited therein for many striking optical, phononic, biomedical, diagnostic and therapeutic applications in the physical literature. Recent studies have revealed the deep and intriguing connection between the plasmon resonance and the spectral study of the Neumann-Poincaré operator [2,3,5,12,22,23,31,42,45]. In addition, there are many theoretical understandings and conceptual proposals about plasmonic devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer to [10,11,36,47,50,53] and the references cited therein for many striking optical, phononic, biomedical, diagnostic and therapeutic applications in the physical literature. Recent studies have revealed the deep and intriguing connection between the plasmon resonance and the spectral study of the Neumann-Poincaré operator [2,3,5,12,22,23,31,42,45]. In addition, there are many theoretical understandings and conceptual proposals about plasmonic devices.…”
Section: Introductionmentioning
confidence: 99%
“…In [8], by analyzing the imaginary part of the Green function, it is shown that one can achieve super-resolution and super-focusing by using plasmonic nanoparticles. In [2,3,12], it is shown that the plasmon resonance concentrates and localises at high-curvature places, which can provide potential application in super-resolution imaging of plasmon particles. We would also like to mention in passing some related studies on plasmonic cloaking [5, 9, 16, 22, 25, 38-41, 46, 56].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their connection to the SPR discussed above, the quantitative properties of the NP eigenvalues have been extensively studied in recent years; see e.g. [3,16,17,30,36,43,44] and the references cited therein. As is mentioned earlier that the SPR mainly oscillates around the material interface ∂D, which is rigorously justified in [12].…”
mentioning
confidence: 99%
“…The CALR has been extensively investigated. We refer to [4,6,9,11,15,20,21,29] for the relevant study in acoustics, [8,10,17,18,19,27,28,24] for elastic system and [3,2,1,7,13,14,15,25,26,31,32,33,34,36,37,38] for the Maxwell system.…”
mentioning
confidence: 99%